2000
DOI: 10.1152/ajpregu.2000.279.3.r1010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of severe normocapnic hypoxia on renal function in growth-restricted newborn piglets

Abstract: To examine the effects of intrauterine growth restriction and acute severe oxygen deprivation on renal blood flow (RBF), renovascular resistance (RVR), and renal excretory functions in newborns, studies were conducted on 1-day-old anesthetized piglets divided into groups of normal weight (NW, n = 14) and intrauterine growth-restricted (IUGR, n = 14) animals. Physiological parameters, RBF, RVR, and urinary flow, were similar in NW and IUGR piglets, but glomerular filtration rate (GFR) and filtration fraction we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In a previous study with extensive surgical interventions, including opening the abdominal cavity, craniotomy, and ureter cannulation after retroperitoneal preparation along with 5 h of experimental performance, sham-operated newborn piglets showed no significant differences in ABP with only a slight increase in heart rate (by 20%). This corresponded to a comparatively moderate increase in circulating catecholamines (epinephrine by 73%, norepinephrine by 66%) (26). This elevation in circulating catecholamines was markedly blunted compared with a rather mild hypoxic exposure.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In a previous study with extensive surgical interventions, including opening the abdominal cavity, craniotomy, and ureter cannulation after retroperitoneal preparation along with 5 h of experimental performance, sham-operated newborn piglets showed no significant differences in ABP with only a slight increase in heart rate (by 20%). This corresponded to a comparatively moderate increase in circulating catecholamines (epinephrine by 73%, norepinephrine by 66%) (26). This elevation in circulating catecholamines was markedly blunted compared with a rather mild hypoxic exposure.…”
mentioning
confidence: 86%
“…Furthermore, an improved capacity of newborn IUGR piglets to withstand severely disturbed renal oxygenation has been reported (26). Until now, the effects of IUGR on the cerebral autoregulatory response and cerebral oxygen uptake during gradual reduction of the cerebral perfusion pressure have not been determined.…”
mentioning
confidence: 99%
“…Millard et al (27) reported that administration of indomethacin to fetal sheep caused a significantly greater decrease in renal blood flow when fetal hypoxia was induced. Interestingly, Bauer et al (28) demonstrated that in growth-restricted newborn piglets, the decrease in renal blood flow in response to severe hypoxia was smaller when compared with normally grown newborns, suggesting that adaptations in the growth-restricted fetal kidney improve its capacity to maintain renal blood flow during hypoxia. Based on data from the present study, it would be pertinent to determine the effects of blockade of the EP 2 /EP 4 receptor subtypes on renal blood flow and renin mRNA expression in the growthrestricted fetus.…”
mentioning
confidence: 99%
“…In a previous study with extensive surgical preparations, including opening the abdominal cavity, craniotomy, ureter cannulization after retroperitoneal preparation and up to 5 h experimental performance, sham‐operated newborn piglets showed no significant differences in arterial blood pressure and only a slight increase in heart rate (by 20%). This corresponded to a comparatively moderate increase in circulating catecholamines (adrenaline (epinephrine) by 73%, noradrenaline (norepinephrine) by 66%) (Bauer et al 2000). This elevation in circulating catecholamines was markedly blunted compared with a rather mild hypoxic exposure.…”
Section: Discussionmentioning
confidence: 99%